2015
DOI: 10.1149/2.0331510jes
|View full text |Cite
|
Sign up to set email alerts
|

Potentials Near a Curved Anode Edge in a PEM Fuel Cell: Analytical Solution for Placing a Reference Electrode

Abstract: We consider a PEM fuel cell with concentric circular electrodes: the small anode and the large cathode. A model for in-plane distributions of the cathode overpotential η c and the membrane potential in the anode-free region of the cell is developed. Mathematically, the problem reduces to the axially symmetric Poisson-Boltzmann equation for η c . An approximate analytical solution shows that |η c | exhibits rapid decay to zero with the radius, while | | grows to the value of |η 0 c |, the cathode overpotential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…It is also evident, that the rate of η decay with this distance is maximal at the symmetry axis x of the problem. It has been shown that the membrane potential Φ increases with the distance from the tip, reaching the value of η 0 as η ( x ) approaches zero (Figure b). Thus, by placing a hydrogen‐fed reference electrode at the point where η ( x ) ≅ 0, one can measure Φ ≅ η 0 (Figure b).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…It is also evident, that the rate of η decay with this distance is maximal at the symmetry axis x of the problem. It has been shown that the membrane potential Φ increases with the distance from the tip, reaching the value of η 0 as η ( x ) approaches zero (Figure b). Thus, by placing a hydrogen‐fed reference electrode at the point where η ( x ) ≅ 0, one can measure Φ ≅ η 0 (Figure b).…”
Section: Introductionmentioning
confidence: 95%
“…In the anode‐less area, the cathode overpotential is described by the Poisson–Boltzmann (PB) equation, which in dimensionless form reads , truenormalΔ η ~ =normalsinh( η ~ ) …”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Ubong et al [23] reported in their 3D modeling study for a PEMFC unit cell using Comsol Multiphysics software the following values for the kinetic parameters involved in Butler-Volmer equations: The electrochemical activation potential η act between CL solid matrix and PEM electrolyte at anode and cathode (at boundaries IV and V) was defined as [24]:…”
Section: Governing Equations In Comsol Multiphysics Interfacesmentioning
confidence: 99%